Identification of di-o,o′-Cl-, mono-o-Cl- and non-o-Cl-substituted PCB congeners in Neckar river fish - Haiber, Georg; Schöler, Heinz Friedrich (Chemosphere, 1994)
Di-o,o′-Cl-, mono-o-Cl- and the highly toxic non-o-Cl-substituted PCBs could be found in muscle tissue of the six different fish species eel, perch, roach, chub, bleak and barbel. The PCBs were identified by GC/ECD and GC/MS. The measured PCB concentrations were transformed in TEQ-values for better risk assessment. In eel the average PCB concentration (the sum of the congeners # 28, 52, 101, 138, 153, 180) is 423 μg/kg and 0.36 TEQ/kg for mono-o-Cl- and coplanar PCBs. Because of the fat content in eel the average PCB contamination is about four times higher than in the other fish. None of the PCB values for # 28, 52, 101, 138, 153 and 180 exceed the German maximum acceptable residue limits for food (SHmV) though the toxic PCB # 77, 126 and 169 are not taken into consideration.